Impact assessment of 5g technology on economic sectors and proposal of a roadmap for 5g service deployment in Vietnam - Tuan, Tran Minh; Hung, Nguyen Phi; Hoa, Dang Thi; Bac, Nguyen Gia; Vu, Dong Hoang; Anh, Dao Thi Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
In the past, the fifth generation (5G) mobile network in Vietnam has been gradually deployed in tune with the world and it is ready for commercialization in the coming time. Therefore, actively researching, evaluating potential applications, and forecasting the impacts of 5G mobile technology on economic sectors will serve as a basis for proposing orientations for the development of potential 5G applications in Viet Nam. Making contributions to the policy makers and telecommunications providers to have a referenced landscape of 5G situation development in Vietnam before it is commercially deployed on a large scale. With over 2000 surveyed samples on the 5G potential applications from the user’s point of view to identify trends and social needs for the new 5G services. Using an IO analysis model on economic sectors of Vietnam to forecast the impacts of 5G on socio-economic industries at the time of 2025 and 2030, thereby proposing some orientations in the roadmap of exploring the potential 5G applications in Vietnam. The article content shows a research part of the state-level project: "Research to propose a roadmap and policy for 5G deployment in Vietnam". Code: DTLDCN-10/20. Code: 21012501